The associations between cognitive function and depressive symptoms among older Chinese population: A cohort study - Yang, Fan; Fu, Mingqi; Hu, Qitu; Guo, Jing (Frontiers in Psychiatry, 2023)
With the rapid development of society, population aging has become one of the major challenges worldwide. This study aims to assess the effects of baseline cognition performance, current cognitive function, and cognitive decline on the follow-up depressive symptoms. This study retrieves data from participants aged 65 years and older of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), Wave 2014-2018. A total of 1,627 participants were included from 7,192 participants in wave 2014. Multivariate regressions were performed to estimate the associations. Our results indicated that the baseline cognitive function is not related to follow-up depressive symptoms, but current cognitive function was associated with depressive symptoms. Participants who had great cognitive decline were more likely to have depression. Covariates, including marital status, economic status, physical activity, and recreational activity, were also related with the subsequent depressive symptoms. Such findings suggest slowing cognitive decline is an effective way to prevent depressive symptoms in the old adults to make them more healthily and happily.